Voltammetric Determination of Adenovirus Specific DNA Sequence Using Self-Assembled Dimercapto-Succinic acid Monolayer on Gold Electrode - Liu, Fenghai; Wang, Maoqing; Du, Xiaoyan; Qu, Zhangyi; Liu, Ying; Zhai, Xiaoguang; Li, Yongquan; Wang, Kaili; Liu, Changfu (Asian Journal of Chemistry, 2010)
A novel electrochemical DNA biosensor for the detection of adenovirus specific DNA sequence is presented in this paper. Dimercapto succinic acid was self-assembled on gold electrode surface and amino group ended single-strand DNA (NH2-ssDNA) probe was immobilized covalently to carboxylic group of dimercapto succinic acid monolayer in the presence of 1-ethyl-3-(3- dimethylamino-propyl)carbodiimide and N-hydroxysulfosuccinimide sodium salt as linker. The NH2-ssDNA probe was hybridized with complementary ssDNA in solution. Meanwhile, Co(phen)33+ as electrochemical hybridization indicator was intercalated into double stranded DNA (dsDNA) to form a dsDNA/Co(phen)33+ system on the gold surface. Differential pulse voltammetry was utilized to detect an increase of redox peak current of Co(phen)33+ on dsDNA/ Au electrode. Using this method, an adenovirus specific DNA sequence could be quantified over the range from 1.03 × 10-9-2.06 × 10-7 mol/L-1. The detection limit is 5.23 × 10-10 mol/L-1.